PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI DI KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI SULAWESI SELATAN - Zulhimmah Mukhlis; Risma Niswaty; Andi Aslinda; Herlina Sakawati; Jamaluddin Jamaluddin (Universitas Khairun, 2023)
This study aims to determine the effect of the environment on employee work motivation at the Office of the Investment and One Stop Service Office of South Sulawesi Province. This study uses quantitative research methods. Data collection techniques were carried out through observation, questionnaires and documentation. The population in this study were 83 people. The sampling method is saturated sample. Data obtained from the program through the SPSS 25 application which consists of validity tests, descriptive data analysis techniques and inferential statistical data analysis. The results showed that the work environment variable was in the good category and work motivation was in the good category. Based on the results of the inferential analysis, it shows that there is a significant influence between the work environment on the work motivation of employees at the Office of the Investment and One Stop Service Office of South Sulawesi Province.